TINJAUAN DAN PANDANGAN HUKUM TERHADAP PERKAWINAN YANG TIDAK TERCATAT PEMERINTAH SERTA DAMPAKNYA SECARA EKONOMI - Tulus Prijanto (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this research is to find out how the legal review and views of unregistered marriages by the government are still widely practiced by the community, where if something happens that causes the marriage to be terminated, it will have an impact on several things and one of them is in the form of economic impact (material /legacy). This research is a qualitative research using literature study method which is supported by various relevant references, especially journals related to the research theme. The results showed that marriages that were not registered by the government had a large legal impact, especially on the proceeds of marriage, on the status of the child resulting from marriage. This marriage is valid in the eyes of religion but has no legal force that can harm both women and children, because they cannot make legal claims against the husband when the husband does not provide a living and the husband divorces his wife, and is not even entitled to inheritance if the husband dies. Of course, the economic impact for the wife, especially for their children, is very large. The husband or the father of the child can leave all obligations for all living expenses both to the ex-wife and the child he has left behind. Thus, the ones who will become the biggest economic victims are their offspring from a legal perspective.